Makna Kritik Sosial dalam Lirik Lagu “5” .Feast - Putra, Dimas Maulana; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Communication is an activity that humans have always done. Communication can be done verbally or non-verbally. One form of communication that is developing at this time is the art of music. Music is a very influential medium for voicing social and political criticism. Therefore, music is often used as a tool of resistance, exposing social realities and injustice. This research aims to analyze the meaning of social criticism contained in the lyrics of the song